Comparative Study of the Financial Performance on Pharmaceutical and Healthcare Companies Before and During the Covid-19 Pandemic - Sakina Ichsani; John Henry Wijaya; Susanto Hendiarto; Dede Hertina (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
The Covid-19 pandemic has disrupted supply chains both locally and globally, financial market volatility has faltered, there have been fluctuations in demand and has had an impact on the pharmaceutical and healthcare sectors. The increasing public awareness of the importance of maintaining health has made the products produced by the pharmaceutical and health sectors become products that are sought after by the public. The purpose of this study was to determine the financial performance of pharmaceutical and health companies before and during the COVID-19 pandemic using profitability ratios and solvency ratios. The results showed that there was no difference in financial performance using the profitability ratio approach, namely net profit margin, return on assets and return on equity. Meanwhile, by using the solvency ratio approach with debt to equity ratio and debt to asset ratio proxies, there are differences before and during the Covid-19 pandemic. The suggestion for this research is for pharmaceutical and health companies to always pay attention to their financial performance which in this study is concentrated on the solvency ratio because there are differences in performance before the pandemic and during the Covid-19 pandemic. Suggestions for other researchers are to increase the research period and add other financial ratios in order to enrich and expand the scope of research.